Associations of oral hygiene with incident hypertension and type 2 diabetes mellitus: A population based cohort study in Southwest China. Issue 4 (7th March 2022) - Wang, Yiying; Jiang, Yizhou; Chen, Yun; Yu, Lisha; Zhou, Jie; Wang, Na; Liu, Tao; Fu, Chaowei
Abstract: Oral health has been previously reported to be related with cardiovascular diseases (CVD). This study aimed to evaluate whether oral hygiene could reduce the risk of incident hypertension and type 2 diabetes mellitus (T2DM) in a population‐based cohort. A total of 9280 people aged 18 years or above in Guizhou province were recruited from November 20th, 2010 to December 19th, 2012. Sociodemographic characteristics, lifestyles, anthropometric measurements, oral health status and care were collected by trained interviewers. The occurrences of hypertension and T2DM were ascertained until 2020. Cox proportional hazard models were used to evaluate the associations between oral hygiene and the occurrence of hypertension and T2DM, respectively. Compared with almost no tooth brushing, tooth brushing at least twice a day was associated with a 45% reduction (HR: .55; 95% CI: .42–.73) in hypertension events and reduced diabetes risk by 35% (HR: .65; 95% CI: .45–.94). For hypertension, those associations tended to be more pronounced in participants with Han ethic, or living in urban area, while those aged less than 60 or without baseline hypertension were more likely to have T2DM when they brush teeth less than twice a day. Frequent tooth brushing was associated with reduced risks of incident hypertension and T2DM. Tooth brushing at least twice a day may prevent future hypertension and T2DM events.